Ultrahigh-strength CoNiV medium-entropy alloy wire with double-phase laminar structure and preparation method of CoNiV medium-entropy alloy wire

By forming a biphasic layer structure in CoNiV medium entropy alloy, including the FCC phase and the κ phase, combined with process steps such as hot rolling, homogenization, cold rolling, annealing and cold drawing, the existing high-strength steel wire is solved, and the effect of tensile strength exceeding 2.5GPa and elongation is not less than 5%.

CN119530631APending Publication Date: 2025-02-28ANSTEEL BEIJING RES INST CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411689794.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The strength of the existing high-strength steel wire has not yet exceeded 2500MPa, and the design idea of ​​Fe element as a single main element makes its strength prospects limited, making it difficult to regulate performance by changing the organizational structure.

Method used

CoNiV medium entropy alloy is used to form an ultra-high strength biphasic layer structure by controlling the alloy composition and process parameters, including the FCC phase and the κ phase, and is prepared through process steps such as hot rolling, homogenization, cold rolling, annealing and cold drawing.

Benefits of technology

The tensile strength of the CoNiV entropy alloy wire material exceeds 2.5GPa and the elongation rate is not less than 5%, breaking through the ultimate strength of traditional steel wires and maintaining high plasticity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119530631A_ABST
    Figure CN119530631A_ABST
Patent Text Reader

Abstract

The invention relates to an ultrahigh-strength CoNiV medium-entropy alloy wire with a double-phase lamellar structure and a preparation method of the ultrahigh-strength CoNiV medium-entropy alloy wire. The ultrahigh-strength CoNiV medium-entropy alloy wire comprises, by atomic percent, 30%-35% of Co, 30%-35% of Ni and 30%-35% of V, and the sum of the atomic percent of all the components is 100%. The preparation method comprises the steps of smelting, hot rolling, homogenization, cold rolling and cold drawing. And before cold drawing and after cold rolling, the plate is subjected to annealing treatment, specifically, the plate is subjected to annealing treatment in vacuum after cold rolling, the annealing temperature is 850-900 DEG C, the annealing time is 5-15 min, and then water quenching is conducted. The mechanical properties that the tensile strength of the CoNiV medium-entropy alloy wire exceeds 2.5 GPa and the ductility is not smaller than 5% are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal materials, and in particular to a CoNiV medium-entropy alloy wire with an ultra-high-strength dual-phase lamellar structure and a preparation method thereof. Background Art

[0002] Bridge cables, aircraft carrier arresting cables, tire cords and other civil and military fields require a large number of reliable high-performance wires, which need to have ultra-high strength and plasticity. With the advancement of science and technology, the demand for high-performance wires is increasing. First, high strength and plasticity can improve the safety of components and protect people's lives; second, higher strength is also conducive to reducing material usage and meeting lightweight requirements.

[0003] Chinese patent application publication number CN 102181786 A and CN 102634730 A respectively introduce the preparation methods of 1670MPa and 1860MPa bridge cable steel wires. The strength of the finished steel wires is less than 2000MPa, which is difficult to meet the increasing demand for bridge cable strength in modern bridge construction. Chinese patent application publication number CN 109280853 A introduces a preparation method for ultrafine bainitic steel wire. Although the steel wire prepared by this method has good strength and plasticity, its strength is still at the 2000MPa level. China's authorization announcement number CN 109628837 B discloses an ultrafine bainitic bridge cable steel and its preparation method. The tensile strength of the steel wire prepared by this method is 1800-2100MPa. At present, the strength of high-strength steel wire has not yet exceeded 2500MPa. In addition, the design idea of ​​using Fe as the single main element makes its strength prospects very limited, because it is difficult to regulate the performance by changing its organizational structure. Medium / high entropy alloys are a new type of alloy that has emerged in recent years. This type of alloy contains at least three main elements and has typical high entropy effect, hysteresis diffusion effect, cocktail effect and lattice distortion effect, which makes it have very excellent comprehensive performance. At the same time, although it usually forms a single solid solution phase at high temperature due to the high entropy effect, it is easy to form a second phase at medium and low temperatures due to the large number of constituent elements. The emergence of these second phases helps to further improve the mechanical properties of medium / high entropy alloys. Therefore, using medium / high entropy alloys as raw materials for wire processing helps to break through the ultimate strength of traditional steel wire. Summary of the invention

[0004] The present invention aims to overcome the current dilemma of high strength and poor plasticity of cold-drawn wires, and provide an ultra-high strength dual-phase lamellar structure CoNiV medium-entropy alloy wire and a preparation method, so as to achieve a tensile strength of CoNiV medium-entropy alloy wire exceeding 2.5GPa and an elongation of not less than 5%.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] Ultra-high strength dual-phase lamellar structure CoNiV medium entropy alloy wire, the alloy components are composed of Co30%~35%, Ni 30%~35%, V 30%~35% in atomic percentage, and the sum of the atomic percentages of each component is 100%. The role of the V element is to increase the atomic radius difference of the alloy system and enhance the yield stress. The Ni element can increase the fluidity of the system during smelting and stabilize the FCC phase. The Co element can also stabilize the FCC phase structure, while promoting the formation of the κ phase and promoting precipitation strengthening.

[0007] The tensile strength of the alloy wire exceeds 2.5 GPa, and the elongation is not less than 5%.

[0008] The preparation method of the ultra-high strength dual-phase lamellar structure CoNiV medium entropy alloy wire includes the following process steps: smelting, hot rolling, homogenization, cold rolling, and cold drawing; before cold drawing and after cold rolling, the plate is also annealed, and the specific contents include:

[0009] 1) Melting: The components are prepared according to the designed atomic ratio of each component of the alloy, and arc melting is carried out under argon protection. The vacuum degree in the furnace is less than or equal to 5×10 -3 Pa, argon gas pressure is 4-6MPa; smelting current is 250-330A, and a rectangular ingot with a size of (10-15)mm×(10-15)mm×(100-120)mm is obtained by suction casting, wherein the raw materials of each component of the alloy are high-purity solid particles with a purity greater than 99.98% to avoid the introduction of impurities, and the smelting process is repeated 3-5 times before suction casting.

[0010] The ingot is subjected to hot rolling, homogenization, cold rolling, annealing and cold drawing to obtain a CoNiV medium entropy alloy wire with a dual-phase lamellar structure.

[0011] 2) Hot rolling: Keep warm at 1100-1150℃ before hot rolling, keep warm for 25-45min after reaching the temperature, and then carry out hot rolling. The final rolling temperature is 900-1050℃. Hot rolling adopts multiple passes, and the reduction of single pass is 1-2mm. The total reduction of hot rolling is not less than 40%.

[0012] 3) Homogenization: After hot rolling, the plate is homogenized in a vacuum at 1100-1200°C for 2-5 hours, followed by water quenching.

[0013] 4) Cold rolling: After homogenization, the plate is subjected to multiple cold rolling processes, with a single-pass reduction of 0.5 to 1.5 mm and a total cold rolling reduction of not less than 80%.

[0014] 5) Annealing: After cold rolling, the plate is annealed in vacuum at a temperature of 850-900°C for 5-15 minutes, followed by water quenching.

[0015] 6) Cold drawing: Use wire cutting to cut the annealed plate into strips of (1-2) mm × (1-2) mm × (300-500) mm, followed by multiple cold drawing processes, with a single pass pressing amount of (0.02-0.05) mm and a total cold drawing amount of not less than 90%.

[0016] The invention discloses a method for preparing a CoNiV medium entropy alloy wire with an ultra-high strength dual-phase lamellar structure. The prepared CoNiV medium entropy alloy wire has a dual-phase lamellar structure of an FCC phase and a κ phase, a tensile strength of not less than 2.5 GPa, and an elongation after fracture of not less than 5%.

[0017] According to the reference [Materials Science and Engineering A: SR Reddy, S. Yoshida, U. Sunkari, A. Lozinko, J. Joseph, R. Saha, D. Fabijanic, S. Guo, PPB Hattacharjee, N. Tsuji, Materials Science and Engineering: A764 (2019): 138226], the highest strength of the medium / high entropy alloy prepared by cold rolling, warm rolling, cold drawing and other methods is only 1.94 GPa, and the elongation after fracture is reduced to 2.4%. It can be seen that the strength of the CoNiV medium entropy alloy wire with an ultra-high strength dual-phase lamellar structure of the present invention is not less than 2.5 GPa, which is the highest tensile strength reported for medium / high entropy alloys at present, and still retains an elongation after fracture of more than 5% (see Appendix Figure 6 ). According to the reference [Materials Science and Technology: Hanchen Feng, Lei Cai, Linfeng Wang, Xiaodan Zhang, Feng Fang, Journal of Materials Science & Technology 97 (2022): 89-100.], compared with common pearlite steel wire, while meeting the performance requirements in terms of strength, the plasticity has been significantly improved.

[0018] Reasons for the process design of the present invention: By pre-introducing the κ phase into the CoNiV alloy before cold drawing, the cold-drawn sample can obtain ultra-high strength while having a certain plasticity. The key is that the lamellar κ phase formed after cold drawing will disperse cracks during the stretching process, which plays a role in delaying stress concentration. In general, the composition segregation of the CoNiV medium entropy alloy prepared by vacuum arc melting is serious, and the composition segregation problem can be effectively alleviated by hot rolling and subsequent homogenization. After homogenization, cold rolling is performed to reduce the thickness of the sheet, introduce deformation, and provide a driving force for subsequent annealing and recrystallization. The κ phase will precipitate when the annealing temperature is less than 900°C, but when the annealing temperature is reduced to below 850°C, a brittle and hard σ phase will be generated, resulting in a decrease in both strength and toughness. Therefore, the annealing temperature is selected to be 850-900°C.

[0019] In the ultra-high strength dual-phase lamellar structure CoNiV medium entropy alloy wire of the present invention, the microstructure of the alloy is regulated by controlling the annealing temperature before cold drawing. Figure 1 ), when the annealing temperature is 850℃, it is a dual-phase structure of FCC phase and κ phase. SEM results (see Appendix Figure 2 ) confirmed the presence of some long strips of precipitated phases in the matrix. The subsequent cold drawing caused the equiaxed grain boundaries to break and elongate. In addition, since the long strips of precipitated phases are deformable, they can also be significantly elongated into fibers during the subsequent cold drawing process, forming a dual-phase lamellar structure with the original matrix (see Appendix Figure 3 ). The introduction of this hard phase is the reason why the CoNiV medium entropy alloy wire with a dual-phase lamellar structure has ultra-high strength. Therefore, the annealing temperature has a significant effect on the mechanical properties of the CoNiV medium entropy alloy. The present invention introduces a deformable κ phase into the CoNiV medium entropy alloy by controlling the annealing temperature (850-900°C), thereby improving the strength of the alloy. In addition, the grains after cold drawing are significantly refined, showing the organizational characteristics of nanocrystalline (see Appendix Figure 4 ), and at the same time, the dislocation density is significantly improved, which further improves the strength of the alloy.

[0020] In addition, the fibrous precipitates disperse the crack propagation (see Appendix Figure 5 ), delaying stress concentration, which is the reason for the improvement of plasticity.

[0021] In addition, after hot rolling and subsequent homogenization, the alloy structure composition is evenly distributed, which can eliminate casting defects (such as shrinkage, shrinkage holes, microcracks, etc.), reduce the source of crack propagation, and improve the cold rolling deformation capacity.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] The present invention discloses an ultra-high-strength dual-phase lamellar structure CoNiV medium-entropy alloy wire and a preparation method thereof, which can achieve a tensile strength of more than 2.5 GPa and an elongation of not less than 5%. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is the XRD two-dimensional diffraction pattern of the ultra-high strength dual-phase lamellar structure CoNiV medium entropy alloy wire provided in Example 1 of the present invention after annealing at 850°C for 10 minutes before cold drawing.

[0025] Figure 2 This is a scanning image of the ultra-high strength dual-phase lamellar structure CoNiV medium entropy alloy wire provided in Example 1 of the present invention after annealing at 850°C for 10 minutes before cold drawing.

[0026] Figure 3 This is a scanning image of the ultra-high strength dual-phase lamellar structure CoNiV medium entropy alloy wire after cold drawing provided in Example 1 of the present invention.

[0027] Figure 4 The nanocrystals are formed after cold drawing of the CoNiV medium entropy alloy wire with an ultra-high strength dual-phase lamellar structure provided in Example 1 of the present invention.

[0028] Figure 5 This is a scanning image of the expansion of fibrous κ-phase cracks in the ultra-high strength dual-phase lamellar structure CoNiV medium entropy alloy wire during tensile deformation provided in Example 1 of the present invention.

[0029] Figure 6 This is a tensile stress-strain curve of the CoNiV medium-entropy alloy wire with an ultra-high strength dual-phase lamellar structure provided in Example 1 of the present invention. DETAILED DESCRIPTION

[0030] The specific implementation modes of the present invention are further described below in conjunction with examples. The following examples are used to specifically illustrate the contents of the present invention. These examples are only general descriptions of the contents of the present invention and do not limit the contents of the present invention.

[0031] Table 1 shows the element contents of the alloys of the embodiment; Table 2 shows the preparation process parameters of the alloys of the embodiment; Table 3 shows the mechanical properties of the alloys of the embodiment.

[0032] Table 1 Element composition of alloys in the examples (at.%)

[0033]

[0034]

[0035] Table 2 Preparation process parameters of the alloys of the embodiment

[0036]

[0037] Table 3 shows the mechanical properties of the alloys in the examples.

[0038] Example <![CDATA[R m / MPa]]> <![CDATA[A 50 / %]]> 1 2550 5.3 2 2510 5.6 3 2570 5.1 4 2560 5.2 5 2530 5.4 6 2540 5.38 7 2520 5.5

[0039] Comparative Example 1:

[0040] According to the public literature [Materials Science and Engineering A: SR Reddy, S. Yoshida, U. Sunkari, A. Lozinko, J. Joseph, R. Saha, D. Fabijanic, S. Guo, PPB Hattacharjee, N. Tsuji, Materials Science and Engineering: A 764 (2019): 138226], the highest strength of the medium\high entropy alloy prepared by severe cold deformation of high entropy alloy is only 1.94 GPa, and the elongation after fracture is reduced to 2.4%. Comparing Example 1 with Comparative Example 1, it can be seen that the strength of the alloy prepared by the present invention is increased by 0.66 GPa, and the elongation is increased by more than 2 times.

[0041] Comparative Example 2:

[0042] According to the public literature [Materials Science and Engineering A: SR Reddy, S. Yoshida, U. Sunkari, A. Lozinko, J. Joseph, R. Saha, D. Fabijanic, S. Guo, PPB Hattacharjee, N. Tsuji, Materials Science and Engineering: A 764 (2019): 138226], the single-phase CoNiV wire prepared by cold drawing earlier had a strength of only 1.8 GPa and an elongation of only 3.8%. By comparing Example 1 and Comparative Example 2, it can be seen that the present invention increases the alloy strength by 0.8 GPa and the elongation to 5% by adjusting the organizational structure to a dual-phase lamellar structure.

[0043] The above description is only used to illustrate the technical features of the present invention, and the purpose is only to enable professionals engaged in related material technology to understand the basic content of the present invention, and it cannot be used to limit the scope of protection of the present invention. All equivalent changes or modifications made according to the essence of the present invention should be included in the scope of protection of the present invention.

Claims

1. Ultra-high strength dual-phase layered CoNiV medium entropy alloy wire, characterized in that: The alloy components are composed of Co 30%-35%, Ni 30%-35%, V 30%-35% by atomic percentage, and the sum of the atomic percentages of the components is 100%.

2. The ultra-high strength dual-phase sheet-structured CoNiV medium-entropy alloy wire according to claim 1, characterized in that: The tensile strength of the alloy wire exceeds 2.5 GPa, and the elongation is not less than 5%.

3. The method for preparing the ultra-high strength dual-phase sheet-structured CoNiV medium-entropy alloy wire according to claim 1 or 2, comprising the following process steps: smelting, hot rolling, homogenization, cold rolling, and cold drawing; characterized in that: Before cold drawing and after cold rolling, the plate must be annealed. The specific contents include: after cold rolling, the plate is annealed in a vacuum, the annealing temperature is 850-900℃, the annealing time is 5-15min, and then water quenched.

4. The method for preparing the ultra-high strength dual-phase lamellar structure CoNiV medium entropy alloy wire according to claim 3, characterized in that: The smelting includes: arc smelting under argon protection, with the vacuum degree in the furnace being less than or equal to 5×10 -3 Pa, the argon gas pressure is 4-6MPa; the smelting current is 250-330A, and a rectangular ingot is obtained by suction casting.

5. The method for preparing the ultra-high strength dual-phase lamellar structure CoNiV medium entropy alloy wire according to claim 3, characterized in that: The hot rolling comprises: keeping warm at 1100-1150°C before hot rolling, keeping warm for 25-45 minutes before hot rolling, the final rolling temperature is 900-1050°C, the hot rolling adopts multiple hot rolling passes, the reduction of each pass is 1-2mm, and the total reduction of hot rolling is not less than 40%.

6. The method for preparing the ultra-high strength dual-phase lamellar structure CoNiV medium entropy alloy wire according to claim 3, characterized in that: The homogenization comprises: the hot-rolled plate is homogenized in a vacuum at 1100-1200° C. for 2-5 hours, followed by water quenching.

7. The method for preparing the ultra-high strength dual-phase lamellar structure CoNiV medium entropy alloy wire according to claim 3, characterized in that: The cold rolling comprises: performing multiple cold rolling processes on the homogenized plate, with the reduction amount of each cold rolling process being 0.5 to 1.5 mm and the total reduction amount of the cold rolling being not less than 80%.

8. The method for preparing the ultra-high strength dual-phase lamellar structure CoNiV medium entropy alloy wire according to claim 3, characterized in that: The cold drawing comprises: cutting the annealed sheet into long strips by wire cutting, and then performing multiple cold drawing processes, wherein the pressing amount of a single pass is 0.02-0.05 mm, and the total cold drawing amount is not less than 90%.

Citation Information

Patent Citations

  • Coil rod used for 1670MPa level bridge cable zinc-coated wire and preparation method of coil rod

    CN102181786A

  • Steel wire rod for 1860MPa-level bridge cable galvanized steel wire and manufacturing method thereof

    CN102634730A

  • High-strength and high-toughness bridge cable zinc-coated steel wire and preparation method thereof

    CN109280853A

  • An ultrafine bainitic bridge cable steel and its preparation method

    CN109628837B